Immunological Involvement of MicroRNAs in the Key Events of Systemic Lupus Erythematosus - Chi, Mingxuan; Ma, Kuai; Li, Yunlong; Quan, Min; Han, Zhongyu; Ding, Zhaolun; Liang, Xin; Zhang, Qinxiu; Song, Linjiang; Liu, Chi (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is an archetype autoimmune disease characterized by a myriad of immunoregulatory abnormalities that drives injury to multiple tissues and organs. Due to the involvement of various immune cells, inflammatory cytokines, and related signaling pathways, researchers have spent a great deal of effort to clarify the complex etiology and pathogenesis of SLE. Nevertheless, current understanding of the pathogenesis of SLE is still in the early stages, and available nonspecific treatment options for SLE patients remain unsatisfactory. First discovered in 1993, microRNAs (miRNAs) are small RNA molecules that control the expression of 1/3 of human genes at the post-transcriptional level and play various roles in gene regulation. MicroRNAs (miRNAs) are small RNA molecules that control the expression of one-third of human genes at the post-transcriptional level. The aberrant expression of miRNAs in SLE patients has been intensively studied, and further studies have suggested that these miRNAs may be potentially relevant to abnormal immune responses and disease progression in SLE. The aim of this review was to summarize the specific miRNAs that have been observed aberrantly expressed in several important pathogenetic processes in SLE, such as DCs abnormalities, overactivation and autoantibody production of B cells, aberrant activation of CD4+ T cells, breakdown of immune tolerance, and abnormally increased production of inflammatory cytokines. Our summary highlights a novel perspective on the intricate regulatory network of SLE, which helps to enrich our understanding of this disorder and ignite future interest in evaluating the molecular regulation of miRNAs in autoimmunity SLE.